GAMBARAN FAKTOR-FAKTOR TEKANAN DARAH PADA AKSEPTOR KB HORMONAL DI WILAYAH KERJA PUSKESMAS KEDUNGMUNDU 2016 - Afina Karimatu Zahidah; Ari Udiyono; Mateus Sakundarno Adi (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2017)
The usage of hormonal contraception in Indonesia has increased one of them in the work area of Kedungmundu community health center Semarang city with prevalence in 2015 about 17,9%. The aim of this research is knowing the blood pressure profile of hormonal contraception acceptors in work area of Kedungmundu community health center. This research is descriptive research with observational design and cross sectional approach. Total of sample is 100 hormonal contraception acceptors, 15-45 years old, and selected randomly to be interviewed and measured. The results was hormonal contraception acceptors has high blood pressure (29%); majority of respondents aged early adulthood, 26-35 years old, (43%);used injecting hormonal contraception (75%); had normal nutritional status (55%);had central obesity (66%);Senior High School for the last education (38%);housewife (59%);had salary more than minimum wage work Semarang city (52%);used hormonal contraception for 13-19 years (43%);had no hypertension history (68%);not smoked (100%); exposured by smoke (79%); and did light physical activity (60%). Hypertension incident of the respondents was tend to in late adulthood; had no hypertension history; exposured by smoke;used injection contraception;used hormonal contraception for 13-19 years;had obesity of nutritional status;had central obesity; and had light physical activity. Hormonal contraception acceptors should had sufficient physical activity, avoid of getting exposured by smoke; and controlling blood pressure routinely.